THE EFFECT OF 10% BIOETANOL AND CARBON CLEANER MIXTURES WITH ENGINE GURAH TECHNIQUE ON THE LEVEL OF CO EMISSION IN COROLLA TWINCAM AE 92 - Mujahid Wahyu; Hadi Rahmad (Universitas Sultan Ageng Tirtayasa, 2018)
The purposes of this study were: (1) To determine the effect of using 10% bioethanol mixture on the level of CO emission in corolla twincam AE92; (2) To determine the effect of using carbon cleaner with engine gurah technique on the level of CO emission in corolla twincam AE92; and (3) To determine the effect of using carbon cleaner with engine gurah technique and 10% bioethanol mixture on the level of CO emission in corolla twincam AE92. This research was conducted in the workshop of DISHUB Kediri City. This research is using experimental method. The exhaust emission test used STARGAS 898 Technotest of gas analyzer. The result of study show: (1) There was a decrease in the percentage of CO gas levels of 0.756% when using 10% bioethanol mixture compared to using premium fuel; (2) There was a decrease in the percentage of CO gas levels of 0,268% when using carbon cleaner with engine gurah technique compared the condition before using carbon cleaner; (3) There was a decrease in the percentage of CO gas levels of 1,383% when using carbon cleaner with engine gurah technique and 10% bioethanol mixture compared the condition before using carbon cleaner and 10% bioethanol mixture.